Dobrostan finansowy osób w dojrzałym i starszym wieku w wybranych krajach Unii Europejskiej - Sobolewska-Poniedziałek, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The dynamic nature of demographic changes taking place on the European continent implies the necessity of their analysis, both in the context of causes and effects. The scope of the analysis of these works will take into account first of all the consequences of changes in the age structure of the population, as a result of which the percentage of older people increases. This, in turn, determines that the socio-economic effects of these changes may be on the one hand a barrier to development, and on the other, a chance for new development opportunities. The purchasing power of people in mature and old age, combined with their growing share in the overall population structure, may inspire and cause the emergence of new industries and market segments focused primarily on meeting the needs of older people. The aim of the article is a comparative analysis of financial well-being of older people as a factor affecting the quality of life. The analysis will cover the situation of older Poles in the context of the situation of citizens of other EU Member States. The research will use the method of desk research, data from international statistics, in particular from Eurostat, will be used. In addition, the research methods used in the work will be the description method and critical analysis of domestic and foreign literature
Keywords: financial well-being; elderly people; quality of life; income inequalities